ANALISIS AKUSTIK ALAT MUSIK REBANA - Yeni Purwiyantini; Mahardika Prasetya Aji; Sulhadi Sulhadi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Rebana/tambourine is a traditional musical instrument which is consist of many kinds. Rebana/tambourine was designed manually and received by the manufacturer with a sense of spirit and their own feelings based on their experiences. Human’s sense of hearing can distinguish between high and low tones, but cannot know surely what kind of tone was heard by them. It is very important for a musician to know whether the instrument is already generating correct tones. Because of that, this research was conducted to analyzed the characteristics of sunds frequency in tambourine/rebana. Tambourine/rebana is traditional musical instrument that do not have a standard tone yet as other musical instruments. Each tambourine generated has a difference in each of her tuning. So, it is hopefully that results of this research can be used to decide the standard of tambourine/rebana musical instrument. This research was conducted used software based on android that is android mobile phones. The android mobile phones has been equipped with an android device audio frequency counter which can directly display the value of the frequency of the sound of tambourines observed. By charging every area constantly, can be obtained the resonance frequency value of tambourine directly on the audio frequency counter column. average resonance frequency obtained from this research to tambourine successively from keplak, hadroh and bass is 750-1251 Hz, 681-1189 Hz, 630-1084 Hz, 503- 736 Hz, 270-448 Hz, 227,5-382 Hz, 146-332 Hz, 145-283 Hz. Keywords: Acoustic, tambourine.